Product customisation: a case for the application of a real-time discrete event simulation for traceability in food manufacturing (SIMTrack). (1st December 2008) - Mousavi, A.; Tavakoli, S.
The tracking and traceability of manufactured products, and in particular food products, has a large impact on product customisation and customer satisfaction. In order to enhance the philosophy of product mass customisation in the food industry, this paper proposes a flexible product tracking system that is configurable to the boundaries of any given system, thereby circumventing the difficulties that are encountered by the physical limitations of the present tracking and tracing technologies. The specific objectives are to: minimise the physical, technical and cost constraints by reducing hardware requirements as compared to conventional tracking and traceability systems; facilitate the acquisition of traceability information at the shop-floor level prior to packaging – the collected data will then be transferred to higher levels of production management systems and current business-to-business tracking systems; ensure the flexibility of the proposed software and its configurability to any given system. The information gathered from the proposed system can then be linked with customer inputs, leading to improved customer satisfaction and product quality. In order to achieve the usage of mobile sensors and detectors that are situated at critical positions on the lines and the connection to a real-time production process, simulation tools such as Arena, Witness SIMUL8, etc., are proposed. By using simulation techniques and statistically sound sample observations, it is possible to trace product ingredients in minute detail with 95% confidence.